Death, Fabulation, and Virtual Reality Gaming - Loewen, Jordan (Gamevironments, 2018)
There are few things more common in video gaming than death. The result of falling, stabbing, shooting, draining, and countless other verbs of decay and destruction. Talk of dying in video games often exchanges teleological weight for the more pragmatic machinic signaling of transition back to the actual world from a gamic one. In the relatively short history of the video game medium, there is little evidence that a video game death might trigger any existential self-reflection. This paper argues that contemporary virtual reality technology can change video gaming s relationship to death through its ability to trigger out-of-body experiences. To make this case, I examine the VR games Arizona Sunshine and Deep Sea in light of scientific studies exploring the affective and ideational influence of VR experiences. I then reframe them in light of the virtual philosophy of Henri Bergson, specifically his theorization of fabulation as the religious tendency of the human body, exposing VR s ability to take advantage of various capacities of human embodiment, which amplify the visual and tactile affordances of the video game medium. In doing so, this paper raises the ever-present concerns and questions of all new technology and media as they shape how we think about ourselves in relation to death, embodiment and subjectivity.